Analysis of the Ratio Between Gross Tonnage (GT) and Engine Power (HP) on Mini Purse Seine Vessels at the Coastal Fishing Port (PPP) Larangan, Tegal Regency, Central Java - Suharyanto, Suharyanto; Pramono, Catur Adi; Hermawan, Fajar; Akbar, Mohamad Adha (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2024)
This research was conducted at the Larangan Coastal Fishing Port (PPP) on 15-17 November 2022 and 13-14 October 2023. The research focused on mini purse seine used to catch anchovy. The research method used was survey method and data tracking of vessels and fishing gear. Samples were selected from 50 mini purse seine vessels with brand engines: Mitsubishi, Dongfeng, Tianli, Jiandong, Yanmar, Changfa, Hiundai, JF, DH, and Inda. The engines were dominated by Mitsubishi and Dangfeng, at 36% each. Then the two groups of ships with different engine brands were determined the Gross Tonage and Hourse Power (GT/HP) ratio value of each ship. The ratio value of Mitsubishi engine brand is 0.03-0.11 while that of Dongfeng brand is 0.07-0.30. The mode of GT/HP ratio value of Mitsubishi brand is 0.10 at 33.3% and Dongfeng brand is 0.15 and 0.20 at 16.7% respectively. The average GT/HP ratio value of the Mitsubishi brand is 0.0733 and the Dongfeng brand is 0.1539. The results of previous studies range the value of the GT / HP ratio from 0.11 to 0.28. Both in terms of the mode and the average value of the two engine brands, it is found that the Mitsubishi brand GT / HP ratio value with a mode of 0.10 and an average of 0.0733 < 0.11-0.28. While the Dongfeng brand mode 0.15 and 0.20 and an average of 0.1539 are in the range of 0.11-0.28. Because the GT / HP ratio value is directly proportional to GT and inversely proportional to HP engine power, the Mitsubishi brand tends to use a larger HP engine power. So that the operational cost is higher and vice versa for the Dongfeng brand the operational cost is lower or more economical. In choosing the engine brand, it was found that mini purse seine fishermen in Prohibition used Mitsubishi brand engines for the reasons of ‘strong power’ and ‘rarely broken’ at 35% each. While the Dongfeng brand chose the reason ‘The price is cheap’, ‘easy spare parts’ and ‘rarely broken’ each by 26%.